Changes in Posture and Interactive Behaviors as Infants Progress From Sitting to Walking: A Longitudinal Study - Thurman, Sabrina L.; Corbetta, Daniela (Frontiers in Psychology, 2019)
This longitudinal study assessed how infants and mothers used different postures and modulated their interactions with their surroundings as the infants progressed from sitting to walking. Thirteen infants and their mothers were observed biweekly throughout this developmental period during 10-minute laboratory free-play sessions. For every session, we tracked the range of postures mothers and infants produced (e.g., sitting, kneeling, and standing), we assessed the type of interactions they naturally engaged in (no interactions, passive involvement, fine motor manipulation, or gross motor activity), and documented all target transitions. During the crawling transition period, when infants used sitting postures, they engaged mainly in fine motor manipulations of targets and often maintained their activity on the same target. As infants became mobile, their rate of fine motor manipulation declined during sitting but increased while kneeling/squatting. During the walking transition, their interactions with targets became more passive, particularly when sitting and standing, but they also engaged in greater gross motor activity while continuing to use squatting/kneeling postures for fine motor manipulations. The walking period was also marked by an increase in target changes and more frequent posture changes during object interactions. Throughout this developmental period, mothers produced mainly no or passive activity during sitting, kneeling/squatting, and standing. As expected, during this developmental span, infants used their body in increasingly varied ways to explore and interact with their environment, but more importantly, progression in posture variations significantly altered how infants manually interacted with their surrounding world.